2022
DOI: 10.3390/su14073784
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Eco-Friendly Artwork for Urban Hotels to Attract Environmental Educated Consumers

Abstract: The adoption and implementation of environmental marketing strategies is the hotel industry’s new approach to maintaining a competitive advantage and attracting more green consumers. Indeed, hotels with more sustainable practices and eco-friendly artwork generate more trust and make green consumers more loyal and satisfied. However, there is little prior research which has suggested the mediating role of green artwork between customers’ levels of green perception and their hotel satisfaction. For this reason, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Kapoor et al [37], however, observed that when ecofriendly hotels sponsor social media influencers, their attribute-value message is more effective than a simple recommendation message in influencing travelers' perceptions and intentions. Furthermore, Park and Kang [38] found that customers' green perceptions and their feelings toward eco-friendly artwork influence their intention to visit eco-friendly hotels. Noticeably, the majority of previous studies have mainly focused on foreign visitors or both local and foreign visitors [39,40].…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kapoor et al [37], however, observed that when ecofriendly hotels sponsor social media influencers, their attribute-value message is more effective than a simple recommendation message in influencing travelers' perceptions and intentions. Furthermore, Park and Kang [38] found that customers' green perceptions and their feelings toward eco-friendly artwork influence their intention to visit eco-friendly hotels. Noticeably, the majority of previous studies have mainly focused on foreign visitors or both local and foreign visitors [39,40].…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…Park and Kang (2022) [38] "The Mediating Role of Eco-Friendly Artwork for Urban Hotels to Attract Environmental Educated Consumers".…”
Section: Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study conducted by Li and Grant in 2022 revealed that investments in coastal tourism real estate may experience devaluation due to rising sea levels and global warming. Furthermore, the profitability of specific property types can be affected by the growing environmental awareness among tourists and the shifting preferences towards eco-friendly accommodations (Park and Kang, 2022).…”
Section: Risks Challenges Related To Climate Change and Impacts On To...mentioning
confidence: 99%
“…Hence, it is crucial for companies and organizations to comprehend environmental concepts and integrate them into their supply chain operations (Awan et al, 2021;Panigrahi et al, 2019;Xu et al, 2023). Simultaneously, environmental knowledge is vital for individuals, including business leaders and consumers, enabling them to make informed decisions regarding consumption, investment, and support for eco-friendly business practices (Park & Kang, 2022;Raza & Khan, 2022;Rusyani et al, 2021). One effective method of raising environmental awareness and knowledge is through education (Shelest et al, 2017;Türkoğlu, 2019;Yeşilyurt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%